AB0060 Soluble Glycoprotein VI: A Potential Biomarker for Disease Activity and Platelet Reactivity in Gout. (9th June 2015) - Murphy, C.-L.; Madigan, A.; MacMullan, P.; Bell, L.; Durcan, L.; Fathelrahim, I.; Kavanagh, P.; Geraghty, E.; Helbert, L.; Stephens, K.; Dunne, E.; Kenny, D.; et al.
Abstract : Background: Patients with gout or hyperuricemia are at high risk of cardiovascular mortality. Increased platelet reactivity is a risk marker for adverse cardiovascular events. We previously demonstrated increased platelet reactivity in blood from patients with inflammatory arthritis (IA) 1 . Platelets amplify inflammation in the joint in IA via the collagen receptor, glycoprotein (GP)VI followed by the production of proinflammatory platelet microparticles 2 . When platelets are activated, the GPVI receptor is shed and is detectable in the plasma as soluble GPVI (sGPVI). Objectives: Our hypothesis is that sGPVI would be raised in patients with active gout compared to stable gout versus healthy controls. We also compared serum GPVI levels in those with acute gout versus acute calcium pyrophosphate arthritis (CPP). Methods: Following ethics approval and informed consent, blood was taken from patients with newly diagnosed active gout (n=12). These samples were compared with patients with CPP (n=5), chronic gout (n=17) and healthy controls (n=19). Demographic data including age, gender and VAS pain, VAS disease activity (VASDA) and VAS quality of life scores (VASQOL) were measured. ESR, CRP, fibrinogen and serum urate were assayed. Plasma GPIV samples were prepared by centrifugation at 720 g and then 20000 g to ensure that no platelets or platelet derived microparticles were present in the sample and sGPVI levels were measured by ELISA 3 . Results: Mean serum sGPVI was similar between CPP and chronic gout (7.0±2.8 ng/ml vs 6.3±2.5 ng/ml respectively), but significantly higher in acute gout patients (9.8±4.5ng/ml; p<0.05). Serum sGPVI was significantly higher in acute gout versus healthy controls (3.8±1.3ng/ml). Mann-Whitney U test showed serum sGPVI levels were significantly higher in those with acute gout versus chronic gout versus controls (p<0.05). Spearmans rank correlation test showed no significant correlation between serum GPVI levels and ESR, CRP, VAS pain, VASDA and VASQOL scores. There was weak positive correlation between CRP and VAS Pain (r =0.30), VASDA (r=0.28), VASQOL (r =0.26) (p<0.05). Conclusions: Our data shows that serum GPVI levels are significantly higher in those with acute gout versus those with chronic gout, CPP and healthy controls. There was no correlation between GPVI levels and ESR, CRP and VAS scores but there was weak positive correlation between CRP and VAS scores suggesting an inherent platelet phenomenon independent of inflammatory markers. Thus serum sGPVI may be a marker of both disease activity and platelet reactivity in gout. Platelet hyper-reactivity in patients with gout likely contributes to increased cardiovascular events in these patients. References: Bell L, Madigan A, McMullan P.M. et al Soluble Glycoprotein VI: A Novel Risk Marker for Thrombosis in Patients with Inflammatory Arthritis. ACR Abstract Nov.2012 Boilard E, Nigrovic PA, Larabee K. et al. Platelets amplify inflammation in arthritis via collagen-dependent microparticle production. Science. 2010 Jan 29;327(5965):580-3 Al-Tamimi M, Mu FT, Moroi M et al. Measuring soluble platelet glycoprotein vi in human plasma by ELISA. Platelets. 2009;20:143-149 Disclosure of Interest: None declared